Makna Nilai Piil Pesenggiri Sebagai Pendidikan Karakter dalam Pembelajaran Bahasa Indonesia: Perspektif Pendidikan Islam - Mega Palyanti; Septia Ernita; Risma Peranita; Baharudin (Bulletin of Community Engagement, 2024)
This study aims to examine the meaning of Piil Pesenggiri values as a form of character education in the teaching of the Indonesian language, viewed from the perspective of Islamic education. Piil Pesenggiri, as one of the local wisdom values of the Lampung community, which refers to the collective knowledge, beliefs, and practices of a specific culture or community, encompasses elements such as self-respect, a sense of shame, and responsibility, which are relevant in shaping individuals with noble character. In the context of Indonesian language learning, the application of Piil Pesenggiri values can be an effective approach to strengthening students' character, particularly in terms of communication ethics, appreciation for language, and moral development in line with Islamic teachings. Using a descriptive qualitative method, this study identifies how the integration of Piil Pesenggiri values into Indonesian language learning can enhance students' understanding of the importance of character based on Islamic morality. The results indicate that Piil Pesenggiri's values align with Islamic education's principles, such as trustworthiness, honesty, and responsibility, which play a crucial role in shaping morally and spiritually excellent students. Additionally, implementing these values in Indonesian language teaching significantly contributes to improving character education quality in schools. This study recommends that teachers more intensively integrate local values, particularly Piil Pesenggiri, into teaching as part of a continuous character education reinforcement.